2022
DOI: 10.53730/ijhs.v6ns4.7062
|View full text |Cite
|
Sign up to set email alerts
|

Mapping review of the potential of Tarap Plants (Artocarpus odoratissimus) for health

Abstract: Artocarpus odoratissimus (A. odoratissimus), or tarap fruit in Indonesian, is widely used as traditional medicine because almost all parts have pharmacological properties. The purpose of this review is to examine the health benefits of tarap plants based on published evidence, and also to find out where the potential for these compounds is stored in plant parts. Based on the results of the review, the parts that have the potential as antioxidants are the peel, seeds and flesh of the fruit. The peel also has an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…One notable application is the extraction of bioactive compounds from Marang fruit peels and cores. One study by Abu Bakar et al (2009) identified the presence of bioactive compounds such as phenolics, flavonoids, and antioxidants from the flesh, kernel, and husk of the fruit, highlighting their potential for use in functional food and nutraceutical industries (Yulianti et al, 2022). Moreover, Marang fruit wastes have been also investigated for their potential for the production of eco‐friendly biosorbents or adsorbents for the removal of various toxic compounds, and heavy metals (Lim et al, 2016; Zaidi et al, 2018a, 2019).…”
Section: Current Utilization Of Marang Fruit Wastesmentioning
confidence: 99%
“…One notable application is the extraction of bioactive compounds from Marang fruit peels and cores. One study by Abu Bakar et al (2009) identified the presence of bioactive compounds such as phenolics, flavonoids, and antioxidants from the flesh, kernel, and husk of the fruit, highlighting their potential for use in functional food and nutraceutical industries (Yulianti et al, 2022). Moreover, Marang fruit wastes have been also investigated for their potential for the production of eco‐friendly biosorbents or adsorbents for the removal of various toxic compounds, and heavy metals (Lim et al, 2016; Zaidi et al, 2018a, 2019).…”
Section: Current Utilization Of Marang Fruit Wastesmentioning
confidence: 99%